A Methodological Review of Exploring Turner’s Three-Process Theory of Power and the Social Identity Approach - Ye, Michelle; Ollington, Nadia; de Salas, Kristy (Qualitative Sociology Review, 2016)
Turner’s Three-Process Theory of Power together with Social Identity Theory (SIT) and Self-Categorization Theory (SCT) have been influential in social psychology to examine power-related behaviors. While positivist experimental and survey methods are common in social psychological studies, these approaches may not adequately consider Turner’s constructs due to a comparative lack of ecological validity. Drawing on a methodology-focused review of the existing research of applying aspects of Turner’s theory of power and SIT/SCT, the interpretivist case study approach by using interviews and other data collections is highlighted as an alternative and useful method to the application of Turner’s framework. The applicability of the interpretive case study approach is further emphasized in comparison with the positivist experiments and surveys. This paper also discusses how this new way of exploration may allow us to understand Turner’s work better.